Reading Interests of College Students of the Delfin Albano Memorial Institute of Agriculture and Technology (DAMIAT) - Galiza, Clarinda C. (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the reading interests of the college students of Delfin Albano Memorial Institute of Agriculture Technology (DAMIAT). The researcher made use of the descriptive method of research to determine the reading interests of the selected 193 college students of the school. The students reported that they read to improve their vocabulary; to keep themselves informed; to improve their reading comprehension; and to prepare themselves for class discussion. The reading materials they prefer to read the most to the least are books, newspapers, magazines, journals, pamphlets, and comics, respectively. Results of the Chi-square test for independence showed that the reading interests of the students toward the six reading materials depend on their economic status but not on their sexes, ages, courses, parents’ educational attainment, and residence. The study discussed the implications of these findings.